Alces Gray 1821 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alces Gray 1821 Alces Gray 1821, London Med. Repos., 15: 307. Type Species: Cervus alces Linnaeus 1758 Synonyms: Alce Frisch 1775; Paralces J. Allen 1902. Species and subspecies: 2 species with 4 subspecies: Species Alces alces (Linnaeus 1758) Subspecies Alces alces subsp. alces Linnaeus 1758 Subspecies Alces alces subsp. caucasicus Vereshchagin 1955 Species Alces americanus Clinton 1822 Subspecies Alces americanus subsp. americanus Clinton 1822 Subspecies Alces americanus subsp. cameloides Milne-Edwards 1867 Discussion: Has been regarded as a monotypic genus by most recent workers but Boyeskorov (1999) treated the alces and americanus subspecies groups as species. They are said to be separated by the Yenisei River in Siberia. More information is required on the location and nature of the contact zone, particular in the upper Yenisei, Mongolia, and China. It has yet to be confirmed that both species occur or occurred in Mongolia and China. Genus revised by Peterson (1952); reviewed by Franzmann (1981, Mammalian Species, 154) and Geist (1998). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 653, DOI: 10.5281/zenodo.7316519